2013
DOI: 10.1007/s00221-013-3542-0
|View full text |Cite
|
Sign up to set email alerts
|

Aging of sensorimotor processes: a systematic study in Fitts’ task

Abstract: Though age-related decrease in information-processing capacities is hypothesized to be a prominent cause of behavioral slowing, it has been scarcely systematically studied in goal-directed motor tasks. The present study investigated how the decrease in information processing affects the sensorimotor processes underlying the control of a discrete Fitts' task. The index of difficulty (ID) of the task was manipulated using changes in either target distance (D) or target width (W). In each manipulation, movement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 42 publications
10
57
1
Order By: Relevance
“…These results were comparable to previously reported data in the literature (e.g., Temprado et al, 2013).…”
Section: Age-related Differences In Movement Times (Mts) and Decelerasupporting
confidence: 94%
See 1 more Smart Citation
“…These results were comparable to previously reported data in the literature (e.g., Temprado et al, 2013).…”
Section: Age-related Differences In Movement Times (Mts) and Decelerasupporting
confidence: 94%
“…However, several studies showed that movement durations lengthened more in older than in young participants as ID increased (Haaland, Harrington, & Grice, 1993;Ketcham et al, 2002;Rey-Robert et al, 2012;Teeken et al, 1996;Temprado et al, 2013;Welford, Norris, & Shock, 1969;York & Biederman, 1990). As a consequence, the slope of Fitts' law is generally smaller in young than in older adults (Rey-Robert et al, 2012;Sleimen-Malkoun et al, 2013;Temprado et al, 2013).…”
Section: Previous Findings In the Fitts' Taskmentioning
confidence: 93%
“…This outcome is considered to reflect an increased dependence on limb-target control (Lyons et al 1996;Seidler-Dobrin and Stelmach 1998) which possibly allows older adults to achieve the same level of endpoint accuracy as young adults (Boisseau et al 2002;Ketcham et al 2002;Lyons et al 1996;Welsh et al 2007). The increased dependence on limb-target control in older adults may perhaps be explained by a decline in proprioceptive acuity (Adamo et al 2007;Adamo et al 2009;Herter et al 2014;Kokmen et al 1978;Wright et al 2011;see Goble et al 2009, for a review), impaired efficiency of feedback processing (Rand and Stelmach 2011;Stelmach et al 1988;Temprado et al 2013;Van Halewyck et al 2015b), or both. Indeed, well-documented evidence show that agerelated declines in proprioceptive acuity has led many to suggest that visual feedback becomes increasingly important during accurate aiming in older age (e.g., Coats and Wann 2011;Rand and Stelmach 2011;Terrier et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3 Additionally, y-intercepts and r 2 values in the older women groups corroborate reported age-related differences in SATO. 50,51 For instance, kinematics strategies to reach the target while performing the Fitts task demonstrate that young adults show a richer repertoire of strategies than elderly people, who employ a strategy of submovements Old did not reveal significant effects neither for the interaction "E-I x age" nor for the main factor "E-I". However, the main factor "age" produced significant effects on y-intercept, slope and r 2 [F(6,172)=17.66; p=0.0001; η 2 =0.38].…”
Section: Resultsmentioning
confidence: 99%